2022
DOI: 10.3389/fonc.2022.800639
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram individually predicts the risk for distant metastasis and prognosis value in female differentiated thyroid cancer patients: A SEER-based study

Abstract: ObjectiveDistant metastasis (DM) is an important prognostic factor in differentiated thyroid cancer (DTC) and determines the course of treatment. This study aimed to establish a predictive nomogram model that could individually estimate the risk of DM and analyze the prognosis of female DTC patients (FDTCs).Materials and methodsA total of 26,998 FDTCs were retrospectively searched from the Surveillance, Epidemiology, and End Results (SEER) database from 2010 to 2018 and randomly divided into validation and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The included variables were age, gender, race, grade, AJCC T, AJCC N, radiotherapy, chemotherapy, CEA, marital status, tumor size, DX-bone (Distant metastasis to the bone), DX-brain (Distant metastasis to the brain), DX-lung (Distant metastasis to the lung), DX-liver (Distant metastasis to the brain), total number (from the primary tumors), surgical sites, and histological type. Exclusion criteria: (1) Age less than 18 years old or more than 90 years old;(2) Patients diagnosed by autopsy or death certificate; (3) No information available. Finally, 29367 patients diagnosed with rectal cancer were included in this study, including 3403 patients with liver metastases.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The included variables were age, gender, race, grade, AJCC T, AJCC N, radiotherapy, chemotherapy, CEA, marital status, tumor size, DX-bone (Distant metastasis to the bone), DX-brain (Distant metastasis to the brain), DX-lung (Distant metastasis to the lung), DX-liver (Distant metastasis to the brain), total number (from the primary tumors), surgical sites, and histological type. Exclusion criteria: (1) Age less than 18 years old or more than 90 years old;(2) Patients diagnosed by autopsy or death certificate; (3) No information available. Finally, 29367 patients diagnosed with rectal cancer were included in this study, including 3403 patients with liver metastases.…”
Section: Patientsmentioning
confidence: 99%
“…It has become one of the significant public health problems threatening human health. However, colorectal cancer was often seen as a whole cohort to analyze the risk factors and prognostic factors in many studies (3)(4)(5). There is evidence that colon cancer and rectal cancer differ in incidence, risk factors, mortality, patterns of distant metastasis and clinical prognosis, and the incidence of rectal cancer is higher than that of colon cancer (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…The Surveillance, Epidemiology, and End Results (SEER) ( https://seer.cancer.gov/ ) database is a large public database covering approximately 28% of the U.S. population, providing clinical information about patient demographics, tumor morphology, diagnosis, treatment, and prognosis. 18 Given its extensive records on PTC patients who haven’t undergone treatment, coupled with its exhaustive follow-up information spanning considerable durations, the SEER database presents a viable platform for our investigation. Therefore, in this study, we used the SEER database to statistically analyze the natural history of untreated PTC.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that the prognosis of patients with bone metastasis is usually worse than that of patients with lung metastasis 9 . Distant metastasis is considered the most important prognostic factor for FTC survival 10,11 . Distant metastasis may be the initial manifestation of FTC.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Distant metastasis is considered the most important prognostic factor for FTC survival. 10 , 11 Distant metastasis may be the initial manifestation of FTC. Age and extrathyroidal invasion have been reported to be significant risk factors for FTC distant metastases.…”
Section: Introductionmentioning
confidence: 99%